Role of Technology in Improving Customer Service in Nepal - Dixit, Pratyush Mani Acharya; Pradhan, Sumit (Nepalese Journal of Management, 2025)
This study examines the role of technology in improving customer service in Nepal. Customer experience is the dependent variable. The selected independent variables are ATM, QR code, mobile banking, credit cards, and bundle discount. The primary source of data is used to assess the opinions of respondents regarding ATM, QR code, mobile banking, credit cards, text alert, and customer experience. The study is based on primary data from 125 respondents. To achieve the purpose of the study, a structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of role of technology in improving customer service in Nepal. The study showed a positive impact of ATM on customer experience. It indicates that satisfactory ATM facilities lead to better customer experience. Similarly, the study showed a positive impact of QR code on customer experience. It indicates that more use of QR code results in better customer experience. Likewise, the study also revealed a positive impact of mobile banking on customer experience. It indicates that higher the usage of mobile banking leads to better customer experience. Further, the study observed a positive impact of credit cards on customer experience. It indicates that higher the usage of credit cards leads to exceptional customer experience. In addition, the study observed a positive impact of text alerts on customer experience. It indicates that timely information from text alerts leads to excellent customer experience.